Differences in Levels of Vitamin D, Human Placenta Lactogen (hPL) and Estradiol in Normal Pregnancy and 1st Trimester Abortion - Ismi Mulya Afti; Joserizal Serudji; Fika Tri Anggraini (Faculty of Medicine, Universitas Andalas, 2022)
Vitamin D deficiency is one of the common health problems in the world, around 20-40% occurs during pregnancy (Urrutia-Pereira & Solé, 2015). Abortion or early pregnancy loss in the first trimester has a close relationship with vitamin D deficiency (Hou et al., 2016). This study aims to prove the differences in levels of vitamin D, levels of human Placenta Lactogen (hPL) and levels of estradiol in normal pregnancy and first trimester abortion.This research is a comparative analytic study with a cross sectional approach. The normality test of the data was carried out using the sapiro wilk test and data analysis using the independent T test.The results of the research variables showed that the average levels of vitamin D, Estradiol, and hPL in normal pregnant women were significantly higher than pregnant women who had an abortion in the first trimester, namely (36.577 ng/mL vs 19.120 ng/mL; 626.596 pg/mL vs 246.604 pg/mL; 12.188 g/mL vs 6.786 g/mL) with a value of p<0.05 for the three variables.